Perfecting the Administrative Solution to Labour Disputes. British Columbia Experiment - Joseph, Philip (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1983)
An analysis of the unique nature of the administrative solution to labour disputes in British Columbia experience, with particular reference to section 33 of the Labour Code.